Synthesis of New Isoxazolin - Phenoxathiin Derivatives - Mohamad, Ayad Ahmed; AL-Araji, Suad M (Al-Nahrain Journal of Science, 2018)
The aim of the present work is synthesis of new phenoxathiin derivatives. The 2-(oxoalken-1-yl) phenoxathiin derivatives (3a-3j) obtained from the reaction 2-acetylphenoxathiin with different aromatic aldehyde in the presence of sodium hydroxide. The reaction of 2-(oxoalken-1-yl) phenoxathiin derivatives (3a-3j) with hydroxylamine hydrochloride in ethanolic sodium hydroxide solution to get 2-(isoxazolin-3-yl) phenoxathiin derivatives (4a-4j) which substituted at position (5) in isoxazoline ring with different aryl groups according to aromatic aldehyde used in the preparation of (3a-3j). All the synthesized compounds were characterized by different identification techniques to confirm structure which has been obtained.